Resilience in early adult victims of infidelity in dating - Putri Azzahara Tania; Mutia Mawardah (University of Merdeka Malang, 2025)
Infidelity is a common phenomenon in dating relationships, potentially affecting both men and women. As a deeply painful experience, infidelity necessitates the capacity to endure and adapt to difficult circumstances, commonly referred to as resilience. This study aims to explore the resilience process and the factors influencing resilience among early adult victims of dating infidelity. Employing a qualitative methodology with a phenomenological approach, data were collected through interviews with early adults who have experienced infidelity in their relationships. The research was conducted in Palembang City. Based on the interview findings, it can be concluded that the subjects demonstrated an improved resilience process, enabling them to survive adverse conditions. Additionally, several factors, such as personality traits, were found to influence the subjects’ resilience.